Evaluation of Formulation and Volume Application Rate on the Secondary Pick-Up of Metarhizium acridum (Driver & Milner) Bischoff, Rehner & Humber Conidia on Schistocerca gregaria (Forskål) (Orthoptera: Acrididae) - Alves, Roberto Teixeira; Bateman, Roy Paul (BioAssay, 2013)
Effects of the spray residue of Metarhizium acridum (Driver & Milner) Bischoff, Rehner & Humber, formulated in emulsifiable adjuvant oil and in a mixture of mineral oils, on the mortality of adult desert locusts, Schistocerca gregaria (Forskål), were evaluated. The effects of volume application rates (VARs) and the presence of conidia applied by a spinning disc atomiser, on the spray characteristics of those two kinds of formulations were also evaluated. The conidial formulations were applied to seedlings of wheat by a track sprayer designed to simulate ultra-low volume field spraying in laboratory conditions. No significant differences between the two formulations and between the four VARs on the proportional survival of S. gregaria were revealed, but there were significant differences between doses. The average survival times (AST) of Schistocerca gregaria were calculated and there were significant differences only between doses. When the dose increased, the AST of the insect decreased. Studies on spray characteristics revealed that when the VAR increased, the droplet volume median diameter and the number of droplets/cm2 also increased. Both formulations gave uniform droplet distributions with characteristics of controlled droplet application sprays. When the VAR increased, the droplet volume also increased, the number of conidia/droplet decreased and the number of conidia/cm2 decreased. The emulsifiable adjuvant oil formulation worked as well as the oil formulation in these experimental conditions, and it has a great potential to control insect pests, when sprayed with the appropriate equipment and technique, where the environmental conditions are suitable.